1986
DOI: 10.1002/ijc.2910380306
|View full text |Cite
|
Sign up to set email alerts
|

The immune system during the pre‐cancer and the early cancer period. IL‐2 production by PBL from post‐menopausal women with and without endometrial carcinoma

Abstract: We report on alterations in IL-2 production and cell proliferation following PHA stimulation of peripheral blood lymphocytes (PBL) from stage-I endometrial carcinoma (EC) patients, and on mechanisms involved in these alterations. Our study includes 3 groups: EC patients, post-menopausal women at high risk of developing EC, and age-matched healthy women. IL-2 production was markedly lower in most EC patients than in healthy controls. Varying levels of IL-2 were produced by PBL from women in the high-risk group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1988
1988
1998
1998

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 38 publications
0
6
1
Order By: Relevance
“…A lower production of IFN-Á and IL-2 by PBMC of cancer patients has already been reported by other authors [19][20][21][22] and we could show in several earlier studies that an impaired IFN-Á production becomes more apparent as the tumor load increases [16,23]. However, in all those studies only Th1 cytokines were measured.…”
Section: Discussioncontrasting
confidence: 38%
“…A lower production of IFN-Á and IL-2 by PBMC of cancer patients has already been reported by other authors [19][20][21][22] and we could show in several earlier studies that an impaired IFN-Á production becomes more apparent as the tumor load increases [16,23]. However, in all those studies only Th1 cytokines were measured.…”
Section: Discussioncontrasting
confidence: 38%
“…In one study, an impaired production of TNF was found (Zielinski et al, 1990) and a defective expression and release of the IL-2 receptors (Hakim, 1988), while in another study the production of IL-2 was not diminished (Wanebo et al, 1986). In lymphocyte cultures of patients with endometrial carcinomas a reduced IL-2 production has been described (Yron et al, 1986).…”
Section: Discussionmentioning
confidence: 97%
“…With IL-4, some antitumor effects were first observed in the mouse, the mechanism probably being macrophage activation [176]; these findings have encouraged the first clini cal trials [277],…”
Section: Il-4mentioning
confidence: 99%
“…Reduced IL-2 production by PBMCs seems to be one of the most frequent immune dysfunctions in patients with neoplasms, such as tumors of the gastrointestinal tract [171 -173], urinary bladder [174,175], and endo metrium [176], malignant melanomas [177], and Hodgkin's disease [178],…”
Section: Il-2 and The Il-2 Receptormentioning
confidence: 99%